Ovarian juvenile granulosa cell tumors with Ollier’s disease in children with IDH1 gene somatic mutation - Zhang, Jin; Hua, Renwu; Ma, Lishuang; Liu, Chao; Zhang, Yanxia; Lü, Xuemin; Wang, Tianren; Wan, Naijun (Frontiers in Endocrinology, 2023)
Abstract Objective: To explore the symptoms, treatment and pathogenesis of ovarian juvenile granulosa cell tumors with Ollier’s disease in children. Methods: From October 2019 to October 2020, clinical data were retrospectively analyzed for one case of ovarian juvenile granulosa cell tumors with Ollier’s disease. Whole exome sequencing and Sanger sequencing were used to detect gene mutation in ovarian tumor and chondroma tissue. NADP-dependent isocitrate dehydrogenase-1 (IDH1) and S6 ribosomal protein expression levels in cells transfected with wild-type or mutant plasmid were analyzed by western blot. Results: The 4-year-old girl showed multiple skeletal deformities, bilateral breast development with chromatosis and vulvar discharge. Sex hormone assay suggested that estradiol and prolactin were elevated, and the X-ray of limbs suggested enchondroma. Pelvic ultrasound and abdominal CT revealed a right ovarian solid mass. Pathologic examination of the right ovarian solid mass showed a juvenile granulosa cell type. A c.394C>T (p. Arg132Cys) mutation of the IDH1 gene was detected in both the ovarian juvenile granulosa cell tumors and enchondroma. Transfection of Hela cells with either WT or Mut plasmid caused 4.46 or 3.77 fold overexpression of IDH1 gene compared to non-transfected control cells, respectively. R132C mutation inhibited the phosphorylation of S6 ribosomal protein, which is central to the mTOR pathway. Postoperatively, estradiol and prolactin levels fell to values normal for her age and bilateral breast gradual retraction. Conclusion: The incidence of ovarian juvenile granulosa cell tumors with Ollier’s disease in children may be caused by generalized mesodermal dysplasia, IDH1 gene mutation may play a facilitated role in this process. Surgical operation is the main treatment. We suggest that patients with ovarian juvenile granulosa cell tumors and Ollier’s disease should undergo regular investigation.